Assessment of Positioned Instillation of Contrast Cystography in Children with Recurrent Urinary Tract Infections - Hülya Nalçacıoğlu (Journal of Urological Surgery, 2020)

(untitled)
Objective:Vesicoureteral reflux (VUR) is considered the most important predisposing factor for urinary tract infection (UTI). Renal damage due to VUR, subsequently renal scarring and the possibility of reflux nephropathy warrant early detection of VUR. Our aim was to evaluate the value of positioned instillation of contrast (PIC) cystography in the detection of VUR in children with recurrent UTI and a normal voiding cystourethrography (VCUG).Materials and Methods:PIC cystography was performed in each child with the indication of recurrent UTI with a normal VCUG between June 2015 and November 2017.Results:Thirty-four children (32 girls, 2 boys) aged 7 to 17 years (median, 10 years), were examined. Twenty (58.8%) patients had normal ultrasound and 12 patients (35.3%) had bilateral scars detected using 99mTc-dimercaptosuccinic acid (DMSA). Thirty-one (91.2%) patients were shown to have VUR on PIC cystography. Nine (29%) patients had no renal scar with positive PIC and 3 (12%) patients had scars with negative PIC. Scars were detected in 13 (72.2%) patients with grade I-II VUR, and 4 (30.8%) with grade III-IV VUR had no scars on DMSA. There was no significant difference between the results of PIC and DMSA renal scan. Twenty-six patients (76.5%) with PIC-VUR underwent simultaneous endoscopic injections. During the postoperative follow-up with an average of 12 months, 27 patients showed no evidence of febrile UTIs.Conclusion:Based on our results, PIC cystogram seems to be a good alternative to invasive voiding cystourethrogram in screening children for VUR.